Can "Cleaned and Greened" Lots Take on the Role of Public Greenspace?. (June 2018) - Heckert, Megan; Kondo, Michelle
Cities are increasingly greening vacant lots to reduce blight. Such programs could reduce inequities in urban greenspace access, but whether and how greened lots are used remains unclear. We surveyed three hundred greened lots in Philadelphia for signs of use and compared characteristics of used and nonused lots. We found physical signs of use that might be found in yard space, such as barbeques, picnic benches, and swings, on approximately 10 percent of lots. Logistic regression showed that population density was the only statistically significant predictor of lot use. Findings suggest that greened lots could provide direct use benefits to neighbors.